G360(P) A randomised controlled trial of ready to use therapeutic food (rutf) for moderate/severe acute malnourished indian children with cancer. (12th March 2018) - Tandon, S; Arora, B; Prasad, M; Narula, G; Banavali, S; Gadge, M; Jadhav, A
Abstract : Background: Children with cancer are at increased risk of malnutrition.Early nutrition intervention helps to maintain weight, lean body mass, improved treatment tolerance and QOL.RUTF, with higher recovery rates in pilot studies has brought a paradigm shift in the management of malnutrition.This pioneer trial evaluated the effectiveness of RUTF in prevention of malignancy related weight loss, improvement of micro/macronutrient status, treatment tolerance and QOL. Methods: 70 children (5–15 years) with hematolymphoid and solid tumours were enrolled post the appetite test. Randomization into 1:1 using a computerised table and stratification by type of malignancy. Nutritional status (weight, height, BMI, MUAC, TSF), biochemial analysis, DEXA scan, HRQOL, treatment tolerance evaluated at baseline, 6 weeks and 3 months into study and 6 months follow-up for anthropometry and treatment tolerance. Results: Seventy newly diagnosed MAM/SAM children with cancer with median age 9 years (range, 5–15), M:F 3:1 were randomised into RUTF (37) :control(33) arms. Median protein and calorie intake as well as weight gain at 6 weeks(2.6 kg vs.2 kg) was higher in the RUTF arm compared to controls on standard dietary care. At 6 weeks there was significant reduction of MAM/SAM children ((16 vs. 23, p<0.05))with increment of lean mass in the RUTF arm vs. controls. Vitamin B12 and folate deficiency (33%), vitamin D(63%), 56% and 96% had copper and zinc deficiency respectively, which improved in the RUTF arm. Children on RUTF experienced significant reduction in the episodes of febrile neutropenia (18.9% vs. 30.3%, p=0.06), protocol delays(2.7% vs 30.3%, p<0.05), grade 3/4 neutropenia (40.54% vs. 66.7%, p<0.05), thrombocytopenia(21.6% vs. 30.3%, p<0.05) and anaemia(18.9% vs. 36.36%, p>0.05) beyond 6 weeks. Mean HRQOL scores were better in the RUTF arm at baseline, 6 weeks and 3 months. Conclusion: RUTF is cost-effective in improving nutritional status resulting in higher weight and lean body mass which translates into improved treatment tolerance and QOL.